THE IMPACT OF COASTAL RECLAMATION ON GENDER INEQUALITY AND CHILD VULNERABILITY IN PESISIR PANJANG, BANDAR LAMPUNG - Tabah Maryanah; Nazira Aulia Az-Zahra (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
Coastal reclamation carried out by PT Sinar Jaya Inti Mulya (SJIM) in 2023 along the Panjang Coast, Bandar Lampung, has generated a range of social problems, particularly affecting vulnerable groups such as women and children. Fishing communities that had previously relied on the sea as their primary source of livelihood are now confronted with the loss of fishing grounds, declining fish catches, and the erosion of human resource capacity. This study aims to analyze the impacts of reclamation on gender inequality and child vulnerability using a qualitative case study approach. Data were collected through in-depth interviews with women fishers, male fishers, and representatives of the marine and fisheries office, as well as through direct observation at the reclamation site. The findings reveal that women have suffered from health problems due to air pollution (dust), psychological stress caused by the loss of income, and increased domestic burdens. Meanwhile, children have been significantly affected in terms of health, the loss of both terrestrial and marine play spaces, and psychological distress resulting from drastic changes in their social and ecological environment. Reclamation thus produces not only economic and environmental challenges but also exacerbates gender inequality and heightens children’s social vulnerability. Therefore, it is crucial to integrate gender perspectives and child protection into coastal development policies to prevent future social disasters.